2016
DOI: 10.1080/15384047.2016.1139249
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Ras modulates p38 MAPK-mediated inflammatory cytokine production in glioblastoma cells

Abstract: Inflammation is an important factor promoting the progression of glioblastoma. In the present study we examined the contribution of Ras signaling and TNFa/IL-1b cytokines to the development of the glioblastoma inflammatory microenvironment. Enhanced activation of Ras through de-regulated activation of receptor tyrosine kinases, such as EGFR, PDGFR and cMet, is a hallmark of the majority of glioblastomas. Glioblastoma microenvironment contains high levels of TNFa and IL-1b, which mediate inflammation through in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…Active STAT-3 promotes the recruitment of monocytes via CXCL1, CXCL2 expression, and the induction of a suppressive TME by inducing macrophages to the protumor phenotype (58). In addition to the induction of IL6 Ras-MAPK signaling process includes the activation of p38 MAP kinase (59), which plays a critical role in the induction of TGFb mRNA (60). TGFb is a central pleiotropic cytokine in shaping the immunosuppressive TME, inducing the protumor TAM phenotype, impairing dendritic cell (DC) migration and cytokine sections, inhibiting T-cell responses, and limits the infiltration of leukocytes into the tumor (61).…”
Section: Ras-mapkmentioning
confidence: 99%
“…Active STAT-3 promotes the recruitment of monocytes via CXCL1, CXCL2 expression, and the induction of a suppressive TME by inducing macrophages to the protumor phenotype (58). In addition to the induction of IL6 Ras-MAPK signaling process includes the activation of p38 MAP kinase (59), which plays a critical role in the induction of TGFb mRNA (60). TGFb is a central pleiotropic cytokine in shaping the immunosuppressive TME, inducing the protumor TAM phenotype, impairing dendritic cell (DC) migration and cytokine sections, inhibiting T-cell responses, and limits the infiltration of leukocytes into the tumor (61).…”
Section: Ras-mapkmentioning
confidence: 99%
“…Smad3 is well known as a key regulator of fibrosis in many organ systems, and this is supported by the findings that mice lacking Smad3 are protected against fibrosis in multiple disease models (32)(33)(34). MAPK signaling is able to regulate fibrosis either independently or through cross-talk with Smad pathways (36)(37)(38). It has been reported that both TGF-β1/Smad and ERK/MAPK signaling act as pro-fibrotic pathways accelerated by blood glucose fluctuation (43)(44)(45).…”
Section: Discussionmentioning
confidence: 88%
“…TGF-β1, a fibrotic stimulus, is able to activate Smad proteins (Smad2 or Smad3) directly to cause renal fibrosis (31)(32)(33)(34). Mitogen-activated protein kinase (MAPK) pathways, which comprise extracellular signal-regulated kinase (ERK), c-JUN N-terminal kinase (JNK) and p38 signaling, have been reported to play a role in inflammatory regulation (35,36), and also contribute to the amplification of transmitted signals to promote cellular processes, including proliferation and differentiation, either in the cytoplasm or nucleus (37,38). Thus, the current study aimed to investigate two areas: Firstly, whether there is a cross-talk effect between Smad3 and MAPKs in glomerulosclerosis; and secondly, whether the phosphorylation of MAPKs may be mediated by EP4 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that active MK2 is expressed in clinical glioblastoma specimens and that p38 -MK2 regulates inflammation in the presence of the EGFRvIII and HRasG12V mutants [10,11]. In glioma xenografts, anti-tumour activity of p38 MAPK inhibitor LY2228820 was linked to the reduction of inflammatory tumour microenvironment [12].…”
Section: Introductionmentioning
confidence: 98%
“…Although a number of different mechanisms by which MK2 promotes tumor growth and therapy resistance have been reported, there are limited data on MK2 signaling in gliomas [10][11][12][13][14]. Gliomas are classified in a range from pilocytic astrocytoma (Grade I), to diffusely infiltrating lower-grade gliomas (Grades II-III) and to high-grade glioblastoma (Grade IV) [15].…”
Section: Introductionmentioning
confidence: 99%